Assessment of the diagnostic value of using serum CA125 and GI-RADS system in the evaluation of adnexal masses. Issue 7 (February 2019) - Zheng, Heng; Tie, Yan; Wang, Xi; Yang, Yang; Wei, Xiawei; Zhao, Xia
Abstract : Abstract: Cancer antigen 125 (CA125) is a valuable tumor marker for ovarian cancer. Gynecology Imaging Reporting and Data System (GI-RADS) is proved to be effective at identifying the adnexal masses. We investigated whether the combination of these two methods can improve the diagnostic accuracy of ovarian cancer. We retrospectively analyzed preoperative data of 325 patients diagnosed with suspected adnexal mass, 196 patients with benign ovarian masses and 129 with malignant ovarian cancer (stage I: 34, II: 16, III: 61, IV: 18). CA125 was analyzed using the ARCHITECT system, GI-RADS was evaluated according to the International Ovarian Tumor Analysis consensus nomenclature and definitions. Sensitivities and specificities were also calculated for GI-RADS, CA125 and the combinations. The sensitivity, specificity and accuracy of CA125, GI-RADS were 75.97%, 79.59%, 78.15%, and 90.70%, 90.82%, 90.77%, the combination data were 94.79%, 96.00%, 95.53%. The AUC of combined diagnostic methods was the largest and significantly better compared with each method alone, P  < .001). For stage I-II malignancy, GI-RADS as a single method was superior to CA125. Combined use of serum CA 125 and GI-RADS system improved the identification of adnexal masses at high risk of malignancy and could be used for clinical decision-making.